Characterization of cAMP-Specific Phosphodiesterase-4 (R)-[11C]Rolipram Small Animal Positron Emission Tomography and Application in a Streptozotocin-Induced Model of Hyperglycemia - Thomas, Adam J. (Université d'Ottawa / University of Ottawa, 2011)
Elevated sympathetic nervous system (SNS) tone contributes to excess cardiac mortality associated with type 2 diabetes mellitus (T2DM). Chronic SNS stimulation has detrimental effects to the heart, in particular, with its cell signaling abilities. (R)-[11C]Rolipram small animal positron emission tomography (PET), an noninvasive nuclear imaging modality, was used to assess phosphodiesterase-4 (PDE4) alterations in a high fat diet (HFD), streptozotocin (STZ) induced model of hyperglycemia in rats. Prior to investigation in the animal model, characterization of (R)-[11C]rolipram small animal PET was completed. (R)-[11C]Rolipram binds specifically to PDE4 in the rat heart demonstrated by competitive blockade with (R)-rolipram with the PDE4 enzyme susceptible to saturation with increasing injected masses of unlabeled rolipram. (R)-[11C]Rolipram cardiac retention was elevated by acute norepinephrine stimulation via desipramine pharmacologic challenge. Quantitative (R)-[11C]rolipram PET was highly reproducible in the heart and presents an ideal avenue to investigate PDE4 alterations. (R)-[11C]rolipram small animal PET did not reveal changes in PDE4 expression and activity in STZ-treated hyperglycemic animals compared to STZ-treated euglycemic and control groups. In vitro measures of PDE4 enzyme expression and activity, with or without desipramine, were also not altered between treatment groups. Although (R)-[11C]rolipram small animal PET does not reveal PDE4 alterations in this animal model of diabetes, its utility to assess PDE4 alterations in other over active SNS pathologies, such as heart failure and obesity, remains.
Keywords: Small Animal PET; PDE4; (R)-[11C]Rolipram